DEGREE OF LOCATION OF WORDS IN DICTIONARIES WITH METAPHORICAL MEANING - Bektoshev Otabek Kodiraliyevich; Muminova Mahliyo Ahrorjonovna (Galaxy International Interdisciplinary Research Journal, 2022)
In the language system, the lexical level occupies a central place in terms of nominative and expressiveness. Without the naming function of words, language would not have a communicative feature in society. The national-cultural character of the language is first embodied in the word. The naming function of a word is an expression of the relationship of the content expressed by the word to objects and events in natural existence. By the way, the meaning space (source) of the word exists outside the language. Although the number and quality of word meanings are imprinted in the language system, they appear based on the needs of the community that speaks the language.